Development and evaluation of a new particle tracking solver for hydrodynamic and mass transport characterization of porous media - A case study on periodic open cellular structures - Trunk, Sebastian; Brix, Andreas; Freund, Hannsjörg (Chemical Engineering Science, 2021)
The detailed understanding of local mass transport characteristics in porous catalyst supports is essential for the evaluation of their performance in reaction engineering applications. This applies particularly for the development and assessment of novel concepts such as additively manufactured periodic open cellular structures (POCS). A major drawback of the frequently used Eulerian based mass transport simulation methods is their tendency to overestimate molecular diffusion due to artificial numerical diffusion, especially in the range of high Peclet numbers (boundary-layer dispersion and pure mechanical dispersion regime) that is often encountered in industrial applications.
CRIS-Team WoS Importer:2021-07-30